Factors Affecting Students' Interest in Continuing Study at Higher Education - Wulansari, Endah; Lisnawati; Sahid, Nur; Wahyudi , Riki (International Journal of Education and Teaching Zone, 2023)
This study discusses the factors that influence student’s interest in continuing their studies at public and religious tertiary institution. This type of research is descriptive qualitative research. The subject of this research is SMA Negeri 3 Muaro Jambi, where the population is class XII students, totaling 8 classes, then the sample in this study was XII IPA 1, totaling 30 people. By using the technique of class random sampling cluster a random sampling. The data collection technique used is a questionnaire with 7 questions in the category of strongly agree, agree, disagree and strongly disagree. Then the data is analyzed based on student answers which are then converted based on predetermined categories. The results of data from research that have obtained the fact that the factor that influences students' interest in continuing their studies at public and religious tertiary institutions is the parent factor is 33,3%.